THE EFFECT OF MINDFULNESS INTERVENTION ON BURNOUT IN NURSES - Luh Putu Sukmayanti; Ni Luh Cica Kusuma Dewi; Komang Laksmi Widari; I Gusti Putu Candra Adi Sastrawan (Nurse and Health: Jurnal Keperawatan, 2026)
Background: Burnout among nurses is a significant issue due to high work demands, emotional burdens, and limited resources in hospitals, including private hospitals like Bhakti Rahayu Tabanan. This condition is characterized by emotional exhaustion, depersonalization of patients, and a decreased sense of personal accomplishment, which impacts the quality of nursing care. Several studies over the past five years have shown that mindfulness interventions can reduce burnout and stress levels in healthcare workers, including nurses, whether through face-to-face programs, guided meditation, or mobile applications. Mindfulness helps nurses recognize and accept current experiences without judgment, enabling them to manage work stress more adaptively. Purpose: This study aims to analyze the effect of mindfulness interventions on nurse burnout levels at Bhakti Rahayu Tabanan Hospital. Methods: The planned design is a quasi ‑-experimental study with an intervention and control group. Burnout will be measured using standardized questionnaires (e.g., the Maslach Burnout Inventory) before and after the intervention. The mindfulness intervention will be implemented in several structured sessions over four weeks, consisting of mindfulness exercises focused on breathing, bodily sensations, and emotional acceptance, along with independent home practice. Results: From the results of the Mann-Whitney test conducted on the results of the post-test test of emotional exhaustion between the control and intervention groups, a significance value of 0.011 <0.05 was obtained, depersonalization between the control and intervention groups obtained a significance value of 0.005 <0.05, and the Decrease in Achievement between the control and intervention groups obtained a significance value of 0.018 <0.05 can be interpreted that there is a difference in intent between the intervention group and the control group. The results of the Wilcoxon test conducted on the comparison of the results of the Pre vs Post test of the emotional exhaustion sample obtained a significance value of 0.000 <0.05, depersonalization obtained a significance value of 0.044 <0.05 and Self-Achievement obtained a significance value of 0.005 <0.05 can be interpreted that there is a change in purpose between the intervention group and the control group, it can be interpreted that the mindfulness intervention in nurses has an impact on the emotional exhaustion of nurses. Conclusion: Based on research results, mindfulness interventions have been shown to significantly reduce burnout levels in nurses. The application of mindfulness helps nurses increase self-awareness, manage work stress, and improve emotional regulation, thereby reducing emotional exhaustion, depersonalization, and increasing a sense of accomplishment. Therefore, mindfulness can be used as an effective intervention strategy to maintain mental health and improve nurse performance in the workplace.